2021
DOI: 10.1186/s12944-021-01467-z
|View full text |Cite
|
Sign up to set email alerts
|

Coronary lesion complexity in patients with heterozygous familial hypercholesterolemia hospitalized for acute myocardial infarction: data from the RICO survey

Abstract: Background Although patients with familial heterozygous hypercholesterolemia (FH) have a high risk of early myocardial infarction (MI), the coronary artery disease (CAD) burden in FH patients with acute MI remains to be investigated. Methods The data for all consecutive patients hospitalized in 2012–2019 for an acute MI and who underwent coronary angiography were collected from a multicenter database (RICO database). FH (n = 120) was diagnosed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Smoking, hypertension, hyperlipidemia, inflammation caused by oxidative stress, apoptosis, vascular remodeling, plaque stress, blood-flow shear stress, and diabetes mellitus are all risk factors for ACS [39,40]. Moreover, Yao et al (2021) hypothesized that inflammation and a family history of high cholesterol burden, which begins at a young age, are linked to CAD severity [41]. Similarly, our study revealed that hypercholesterolemia among those with CSA is an independent risk factor for the development of ACS.…”
Section: Discussionsupporting
confidence: 52%
“…Smoking, hypertension, hyperlipidemia, inflammation caused by oxidative stress, apoptosis, vascular remodeling, plaque stress, blood-flow shear stress, and diabetes mellitus are all risk factors for ACS [39,40]. Moreover, Yao et al (2021) hypothesized that inflammation and a family history of high cholesterol burden, which begins at a young age, are linked to CAD severity [41]. Similarly, our study revealed that hypercholesterolemia among those with CSA is an independent risk factor for the development of ACS.…”
Section: Discussionsupporting
confidence: 52%
“…31 Another review of the RICO database in 2021 by Yao et al found that definite FH, as determined by a Dutch lipid clinic network score Open access >6, was associated with more complex coronary lesions, including a higher syntax score, more bifurcation lesions and more multivessel disease. 32 In addition to the clinical outcomes, it is worth noting the healthcare utilisation among patients with FH. We observed a reduced length of stay in the hospital but no significant difference in total charges.…”
Section: Primary and Secondary Clinical Outcomesmentioning
confidence: 99%